BOOK REVIEW: Monica Brînzei, Christopher Schabel (eds.), “The Cistercian James of Eltville († 1393). Author in Paris and Authority in Vienna”, (Studia Sententiarum, 3), Turnhout, Brepols, 2018, 501 p., ISBN 978-2-503-58188-0 - COTOI, Paula (Studia Universitatis Babeș-Bolyai Historia, 2019)
The recently published volume dedicated to the Cistercian monk James of Eltiville is one of the results of a broader research regarding the development of theology at European universities, especially in Paris, during the Late Middle Ages, which generated several projects all having in common not just the topic, but also more or less the same team involving mostly early- and mid-career scholars concerned with medieval philosophy, under the guidance of one or both editors of the current volume. Especially two grants (the THESIS ERC starting-grant and the project Philosophy and Theology in Cistercian Commentaries on the Sentences financed by the Romanian National Authority for Scientific Research) supported the labour of this book, which gathers contributors from the Babeș-Bolyai University of Cluj-Napoca, IRHT Paris, the University of Cyprus, the University of Wisconsin-Madison and the Catholic University of America. Their endeavour is aimed at retracing the “intellectual journey of the Cistercian James of Eltville”, relaying) mostly on his commentary on the Sentences of Peter Lombard. Although his sole academic work, it held the attention of the authors of this volume as it survived in about twenty-five manuscripts, making it one of the most popular texts of the genre in the second half of the fourteenth century and, therefore, a relevant case study.